Factores familiares que inciden en la calidad de vida de adultos mayores durante la pandemia en El Tambo – Ecuador - Paucar Muñoz, Diana Esther (2022)
Older adults constitute the most vulnerable population in times of pandemic due to their physiological and psychological situations, therefore: To determine the family factors that affect the quality of life of older adults in times of pandemic in the Jalupata Community, of the El Tambo Canton – Ecuador, was the research objective fulfilled through a descriptive qualitative design applied to a sample of 40 PAM and 40 of their relatives; With two scales, information was collected which was tabulated and analyzed to obtain results that showed correlation and incidence between the independent variable family factors in dimensions of rights of the elderly, family life and affective ties with the dependent variable quality of life of PAM. In a medium or moderate level range, there is an incidence of part of each of the dimensions of the family factors variable on the quantitative of life variable, but not all the factors analyzed present a relationship with the indicators and dimensions of the dependent variable. This is logical since, to a greater or lesser extent, there are family factors that will be applied by some families and not by others. It was concluded that among the family factors that affect are family protection, contribute economically, integrate older adults into spiritual meetings, work, contribute to satisfy basic needs, provide physical and mental health care, visit them, generate attachment actions. The factors that have a negative impact are physical and psychological abuse on the presence of diseases, integration and psycho-emotional health.